Evaluasi Formulasi Sediaan Mikroenkapsulasi Ekstrak Etanol Daun Mengkudu (Morinda citrifolia L.) - Faleria Destiani Hulu; Razoki Razoki; Refi Ikhtiari (Journal of Pharmaceutical and Sciences, 2026)
Background: Noni leaves (Morinda citrifolia L.) contain bioactive compounds that are easily degraded by environmental factors, thus requiring a delivery system that protects their stability. Microencapsulation is a technique of coating active compounds with a polymer matrix to enhance stability and delivery effectiveness. Objective: This study aimed to evaluate the microencapsulation formulation of ethanolic extract of noni leaves and to determine the extract concentration that produces the most optimal microencapsulation characteristics. Methods: The study was conducted experimentally. The extract was obtained by maceration using 70% ethanol. Microencapsulation was formulated based on sodium alginate with CaCl₂ as a crosslinking agent and chitosan as a coating material. Three formulas were prepared: blank (F0), 2 g extract (F1), and 4 g extract (F2). Evaluations included morphology (SEM), particle size (PSA), moisture content, floating ability, and physical stability over 14 days at room temperature. Results: Microencapsulation was successfully formed with spherical morphology, dominant particle size in the nanoscale (0.04757 µm), moisture content below 5% (F0: 1.5%; F1: 2.4%; F2: 2.3%), floating ability up to 8 hours, and no organoleptic changes during storage. The formulation with 4 g extract (F2) showed the most optimal characteristics compared to other formulas. Conclusion: The microencapsulation method based on sodium alginate, CaCl₂, and chitosan is effective for encapsulating the ethanolic extract of noni leaves. The extract concentration of 4 g produced microencapsulation with the best physical stability, low moisture content, nanoscale particle size, and optimal floating ability.